Boar sperm incubation with reduced glutathione (GSH) differentially modulates protein tyrosine phosphorylation patterns and reorganization of calcium in sperm, in vitro fertilization, and embryo development depending on concentrations. (March 2021) - Rodríguez-Tobón, Ernesto; Fierro, Reyna; González-Márquez, Humberto; García-Vázquez, Francisco A.; Arenas-Ríos, Edith
Abstract: The sperm in the female's reproductive tract undergo changes to fertilize the oocyte (sperm capacitation). These changes are regulated by redox system. However, some assisted reproductive technologies require sperm capacitation under in vitro conditions, though this increases the generation of ROS. Therefore, the aim of this study was to evaluate the effect of GSH as an antioxidant agent during the capacitation of boar sperm [evaluated by calcium compartmentalization, tyrosine phosphorylation (Tyr-P), motility, viability, and acrosomal integrity], in vitro fertilization (evaluated by penetration, monospermy, and efficiency %), and later embryo development (evaluated by cleavage and blastocyst rates, total number of cells per blastocyst and blastocyst diameter). Four experimental groups with different GSH concentrations (0-control, 0.5, 1, and 5 mM) were formed. When 1-GSH was added to the medium, the percentage of capacitated sperm increased after 4 h of incubation; the localization of Tyr-P was modified at 1 h and 4 h of incubation depending on the GSH concentration. Percentages of total and progressive sperm motility also increased at 4 h of incubation, but only in the 5-GSH group compared to control. Viability, acrosomal integrity, and general Tyr-P (Western blot) not differ among the experimental groups. The addition of GSH during gamete interaction increased penetration, monospermy, and efficiency rates in the 1-GSH group compared to the others. However, the effect of GSH was not observed in cleavage and blastocyst rates compared to the control. In conclusion, adding GSH modulates sperm capacitation (by means of calcium compartmentalization and tyrosine phosphorilation pattern) depending on its concentration, and improves IVF output at 1-GSH during gamete interaction. Highlights: Sperm capacitation modulation depends on GSH concentration. One miliMolar-GSH during gamete interaction improves IVF output. GSH concentration during gamete interaction influences blastocyst rates and quality.